(untitled) (Research, Society and Development, 2021)
Histoplasmosis is an endemic disease caused by Histoplasma capsulatum. Co-infection between HIV and H. capsulatum puts patients at high risk of developing the disseminated form of the disease with high lethality. The aim of this study was to conduct a survey containing the latest findings or research conducted in recent years on coinfection. This is an integrative review, using the platforms PubMed, SciELO and LILACS. The following descriptors were crossed with the Boolean OR and AND operator: “HIV”, “AIDS”, “Coinfection”, “Histoplasma” and “Histoplasmosis” in English, Portuguese and Spanish. Inclusion criteria were: full articles published between 2016 to 2021. Exclusion criteria were: duplicate articles, summaries, conference proceedings, reviews, opinion or reflection articles, editorials, articles that did not address the topic and published outside the period of analysis. 25 articles were selected. Regarding the theme of the articles, 68% are studies on the prevalence/incidence of coinfection, 20% deal with clinical manifestations, 8% are studies of diagnostic methods and 4% deal with the genetic diversity of Histoplasma found in HIV patients. There have been no studies on the treatment of co-infection. As for the origin, 68% of the articles are from Latin American countries. This review made it possible to draw an overview of the latest published studies on coinfection. The absence of studies focusing on treatment is perceived and it is necessary to intensify research in this aspect and to carry out serological surveys to determine the real prevalence of Histoplasmosis, as it is still a largely underdiagnosed AIDS-related disease.